Needs for mental health care and service provision in single homeless people - Salize, Hans Joachim; Horst, A.; Dillmann-Lange, C.; Killmann, U.; Stern, G.; Wolf, I.; Henn, Fritz A.; Rössler, Wulf (Social psychiatry and psychiatric epidemiology, 2001)
Background: Specific problems in sampling methodology, case-finding strategies and a standardised needs assessment in mentally ill homeless people have contributed to their being neglected as a mental health care clientele. Method: We assessed a representative sample of homeless people (n=102) in the highly industrialised city of Mannheim (Germany) regarding their prevalence of mental disorders (using the SCID) and their needs for mental health care (using the NCA). Results: We found high prevalences, with 68.6 % of all assessed homeless persons having a current mental disorder. Thus, needs for mental health care were very common, with unmet needs predominating in all problem areas, which was supported by a very weak service utilization. Thus, even in a region with a comprehensive community mental health care network, like the study area, mentally ill homeless people are widely under-provided. Conclusions: Results suggest that the traditional shelter system for homeless people carries most of the mental health care burden for their clientele and must be supported by adequate interventions from community-based mental health care services. A closer connection of both sectors and a better co-ordination of the care offers seems to be a prerequisite for helping to reduce unmet mental health care needs in this specific high-risk group.